Portikus Frankfurt am Main 1987-1997 : Schöne Aussicht 2 - Auffermann, Verena; Baier, Lothar; Boehm, Gottfried; Bruly-Bouabré, Frédéric; Carl, Rüdiger; Cook, Peter; Cooke, Lynne; Douglas, Christoph Graf; Erkmen, Ayse; Fanderl, Helga; Fleck, Robert; Glasmeier, Michael; et al. (Frankfurt am Main : Portikus, 1997)
Ackermann, Franz ; Adams, Dennis ; Armajani, Siah ; Artschwager, Richard ; Balkenhol, Stephan ; Barney, Matthew ; Baumgarten, Lothar ; Bayrle, Thomas ; Blume, Anna & Bernhard Johannes ; Boltanski, Christian ; Borofsky, Jonathan ; Breitenstein, Urs ; Bruly-Bouabré, Frédéric ; Bulatov, Erik ; Bunk, Holger ; C., Sery ; Caramelle, Ernst ; Crayola, Red ; Darboven, Hanne ; Domenig, Gerald ; Dumas, Marlene ; Erkmen, Ayse ; Fabro, Luciano ; Fanderl, Helga ; Feldmann, Hans-Peter ; Fischli & Weiss ; Fritsch, Katharina ; Genzken, Isa ; Gette, Paul-Armand ; Grcic, Tamara ; Grossarth, Ulrike ; Gursky, Andreas ; Hains, Raymond ; Hamak, Herbert ; Hanussek, Christian ; Härtter, Bernhard ; Herold, Georg ; Höfer, Candida ; Hoffmann, Leni ; Immendorff, Jörg ; Jochims, Raimer ; Kabakov, Ilya ; Kawara, On ; Kelley, Mike ; Kelly, Ellsworth ; De Keyser, Raoul ; Kirkeby, Per ; Klingelhöller, Harald ; Knap, Jan ; Levine, Sherrie ; LeWitt, Sol ; Lucas, Sarah ; Männikkö, Esko ; McCollum, Allan ; McQueen, Steve ; Merz, Mario ; Michajlov, Boris ; Mühl, Otto ; Mullican, Matt ; Näher, Christa ; Nauman, Bruce ; Nitsch, Hermann ; Oldenburg, Claes ; Orth, Dietrich ; Otterness, Tom ; Oursler, Tony ; Paik, Nam June ; Peschick, Irene ; Pippin, Steven ; Plas, Nicole Van Den ; Polke, Sigmar ; Posenenske, Charlotte ; Rehberger, Tobias ; Richter, Gerhard ; Roth, Dieter ; Ruff, Thomas ; Samba, Cheri ; Schaerf, Eran ; Schmit, Tomas ; Schneider, Gregor ; Schnyder, Jean-Frederic ; Schütte, Thomas ; Siem, Wiebke ; Slominski, Andreas ; Spalletti, Ettore ; Steiner, Rudolf ; Struth, Thomas ; Stumpf, Manfred ; Tillmans, Wolfgang ; Toroni, Niele ; Trapp, Yvonne ; Tuymans, Luc ; Weiner, Lawrence ; Wesely, Michael ; Wesley, John ; West, Franz ; Wittner, Gerhard ; Wolff, Carl Emanuel
biografie
Duits & Engels
boek